HUBUNGAN KARAKTERISTIK WIRAUSAHA DENGAN KOMPETENSI KEWIRAUSAHAAN PETERNAK SAPI POTONG DI KABUPATEN BULUKUMBA - Immawan Wahyudi Asbara (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
The purpose of this study is to look at the quality and entrepreneurial skills of beef cattle breeders, as well as the relationship between the two. This research uses descriptive qualitative analysis and relationship analysis (correlation). Descriptive analysis is used to describe the entrepreneurial characteristics and entrepreneurial competencies of beef cattle breeders. Relationship analysis is used to determine the relationship between entrepreneurial characteristics and entrepreneurial competence of cattle breeders. Correlation analysis in this study used the Kendal Tau Correlation test. The results of this study indicate that entrepreneurial characteristics have a relationship with the entrepreneurial competence of beef cattle breeders. This suggests that to improve the entrepreneurial competence of farmers, entrepreneurial characteristics also need to be improved.